Does "who I am" influence "how I feel"? Cultural identity and mental health among Hong Kong Chinese adolescents. Issue 2 (24th February 2022) - Wu, Qiaobing; Ou, Ying
Abstract: Securing a clear sense of identity is a critical issue in adolescence, yet the role that cultural identity plays in the well‐being of youths remains unclear. This study aims to examine the relationship between cultural identity and mental health among three groups of adolescents in Hong Kong with different residential backgrounds. Data came from a cross‐sectional survey with 2180 4th–9th grade students in Hong Kong. Cultural identity was assessed by whether the youths identify themselves as local Hong Kong people, mainland Chinese, both Hong Kong and mainland Chinese, or confused about which group to belong to. Mental health was assessed by self‐esteem, mental well‐being, happiness, social anxiety, and depression. Multiple linear regression was performed to examine the relationship between cultural identity and mental health, adjusting for sociodemographic variables. The regression results suggested adolescents with confused cultural identity scored lower in all positive indicators of mental health compared with those with a clear cultural identification. No significant association was found between cultural identity and social anxiety/depression. Uncertainty in cultural identification may be detrimental for the mental health of adolescents living in a multicultural society. Interventions may consider cultivating clear cultural identities among adolescents to promote their mental health.